2017
DOI: 10.5173/ceju.2017.1357
|View full text |Cite
|
Sign up to set email alerts
|

Relationship with immunhistochemical staining extent of CD47 and histopathologic features of bladder tumor

Abstract: IntroductionIt has been shown that CD47 is an important diagnostic and prognostic marker in many cancer types. However, the relationship between CD47 and bladder tumor stage has not been shown in previous studies. To the best of our knowledge, this is the first study investigating the association of CD47 with stages of bladder cancer.Material and methodsSurgical specimens of 175 patients were included in the study. The CD47 staining assessment was performed in the following categories; none, focal, moderate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Yuan et al (9) in patients with hormone receptor negative breast cancer and Lascorz et al (17) colorectal carcinomas showed that overexpression of CD47. In a study conducted by Olcucuoglu et al (7) high CD47 expression was reported to contribute to the evaluation of bladder tumors at various stages. These studies also showed that increased CD47 expression was a poor prognostic factor (7,9,17).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Yuan et al (9) in patients with hormone receptor negative breast cancer and Lascorz et al (17) colorectal carcinomas showed that overexpression of CD47. In a study conducted by Olcucuoglu et al (7) high CD47 expression was reported to contribute to the evaluation of bladder tumors at various stages. These studies also showed that increased CD47 expression was a poor prognostic factor (7,9,17).…”
Section: Discussionmentioning
confidence: 98%
“…In a study conducted by Olcucuoglu et al (7) high CD47 expression was reported to contribute to the evaluation of bladder tumors at various stages. These studies also showed that increased CD47 expression was a poor prognostic factor (7,9,17). Moreover, studies have shown that this increased expression promotes the escape of cancer cells from phagocytosis (8,18).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…CD47 participates in tumor immune escape by combining with SIRPα in other cancers, such as glioblastoma, 42 leiomyosarcoma, 43 osteosarcoma, 44 malignant mesothelioma, 24,45 non-Hodgkin's lymphoma, 46 cervical cancer, ovarian cancer, renal cell carcinoma, [47][48][49] and bladder tumor. 50 Given that CD47 is widely expressed in various cancer types, it represents a potential and widely applicable target for immunotherapy. Using the mechanism of CD47-SIRPα interaction has achieved some success in anti-tumor research.…”
Section: Evolutionmentioning
confidence: 99%
“…Recently, much interest was attracted to the role of CD47 as a regulator of innate immune surveillance when bound to a membrane protein called SIRPα (SHPS-1/BIT/CD172a) on macrophages and other myeloid cells [ 7 ]. Phagocytosis is downregulated when SIRPα on a phagocyte binds with CD47 of the target cell [ 8 ]. Blocking CD47 makes it unable to restrain SIRPα, triggering phagocytosis [ 8 ] and creating an attractive therapeutic target.…”
Section: Introductionmentioning
confidence: 99%